2014
DOI: 10.1007/s11356-014-3847-y
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine, biotransformation, and oxidative stress responses in salmon hepatocytes exposed to chemically induced hypoxia and perfluorooctane sulfonamide (PFOSA), given singly or in combination

Abstract: Abstract. The effects of hypoxia and PFOSA, given singly and also in combination on endocrine, biotransformation and oxidative stress responses were investigated in primary culture of salmon hepatocytes. Hypoxia was induced chemically using cobalt chloride (CoCl 2 ) or deferroxamine (DFO). Primary culture of salmon hepatocytes were exposed to either CoCl 2 (150 µM) or DFO (100 µM), in the presence or absence of PFOSA at 0, 25 and 50 µM for 24 and 48 h. Changes in transcript levels were analysed by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 101 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The environmental impact of PFAS encompasses a range of effects on wildlife. Scientific studies have demonstrated that PFAS can disrupt the endocrine system and interfere with the development and reproduction of animals (White et al, 2011;Olufsen and Arukwe., 2015). Additionally, PFAS have been found to affect the immune system, potentially leading to increased susceptibility to diseases (White et al, 2011).…”
Section: Fate Of Pfas In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental impact of PFAS encompasses a range of effects on wildlife. Scientific studies have demonstrated that PFAS can disrupt the endocrine system and interfere with the development and reproduction of animals (White et al, 2011;Olufsen and Arukwe., 2015). Additionally, PFAS have been found to affect the immune system, potentially leading to increased susceptibility to diseases (White et al, 2011).…”
Section: Fate Of Pfas In the Environmentmentioning
confidence: 99%
“…These complex processes depicted in Figure2underscore the challenges posed by PFAS in the environment and emphasize the importance of understanding their fate and transport dynamics to mitigate their impact effectively(Stahl et al, 2011; Ankley et al, 2021;Savoca and Pace, 2021).The environmental impact of PFAS encompasses a range of effects on wildlife. Scientific studies have demonstrated that PFAS can disrupt the endocrine system and interfere with the development and reproduction of animals(White et al, 2011;Olufsen and Arukwe., 2015). Additionally, PFAS have been found to affect the immune system, potentially leading to increased susceptibility to diseases(White et al, 2011).…”
mentioning
confidence: 99%
“…It suggests the transcriptional repression of STAR by HIF1 as one mechanism for the reduction of testosterone under hypoxia condition. Hypoxia condition in tissues and organs mediated by low oxygen supply is a critical factor that affects many physiological and pathological processes, particularly in the endocrine system (Trayhurn et al 2008, Anju et al 2011, Olufsen & Arukwe 2015. For instance, STAR is necessary for syntheses of steroid hormones (Sewer & Waterman 2003).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…Toxicological investigations have concluded that long-chain perfluorinated compounds (PFCs) (≥6 carbon atoms) have a higher potential for bioaccumulation and inducing toxicological effects relative to shorter homologues. , PFOSA, with eight carbons, has been shown to induce endocrine disrupting effects, developmental malformations, and neurotoxicity. It has additionally been suggested that PFOSA can more readily pass through cell membranes relative to other PFCs . The passage of PFOSA through the placenta and blood-brain barrier has been noted and can increase intracellular levels and induce a high incidence of neurotoxicity, which has largely been attributed to being less hydrophilic .…”
Section: Introductionmentioning
confidence: 99%